From Convenience To Risk: Spreadsheet Characteristics And Shadow IT In E-Government Implementation In Indonesia - Nugraha, Ginanjar; Munir; Dirgantari, Puspo Dewi (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
This study investigates how specific spreadsheet characteristics influence Shadow IT emergence in e-government implementations, examining the digital literacy and organizational context in rural and urban government settings. Employing a mixed-methods approach, this research surveyed 285 government employees across 45 government offices implementing e-government systems in Indonesia. Structural Equation Modeling analyzed relationships between spreadsheet characteristics and Shadow IT adoption. Qualitative interviews with 32 participants provided contextual insights through thematic analysis.Results reveal that spreadsheet flexibility (β = 0.42, p < 0.001) and user autonomy (β = 0.38, p < 0.001) significantly predict Shadow IT adoption. Digital literacy negatively moderates these relationships (β = -0.23, p < 0.01), with lower literacy strengthening the spreadsheet-Shadow IT link. Rural contexts show 34% higher Shadow IT prevalence compared to urban settings.